Implementing WSIS outcomes : experience to date and prospects for the future (United Nations New YorkUS, 2011)
Reviews progress made in implementation since the conclusion of the World Summits on the Information Society in 2003 and 2005. Identifes areas where progress has been made and where progress has been slow since 2005. Identifies obstacles and constraints encountered as well as actions and initiatives to overcome them and important measures for further implementation of WSIS outcomes. Concludes with discussion of new developments since 2005 as well as findings and suggestions in the lead up to the 2015 comprehensive review of WSIS outcomes.
Keywords: INFORMATION SOCIETY